Uso de plantas medicinais e sua potencial interferência no controle da anticoagulação oral em cardiopatas atendidos em clínica de anticoagulação de um hospital universitário - Paula Mendonca Leite (2015)
Currently, cardiovascular disorders have become increasingly common, due tothe reversal of the demographic pyramid and aging population together with increased sedentary lifestyle and bad eating habits. In Brazil, the situation is no different and the use of drugs to treat these disorders has grown. Warfarin is one of the most widely used in oral anticoagulation to reduce the risk of thromboembolic events. However, in spite of being an affordable medicament, drug therapy with warfarin is complex because it has a narrow therapeutic index, it does not follow standard dose response and it has the potential to interact with various medicines, foods and medicinal plants. Plants such as garlic, ginkgo and ginseng have its effects on blood homeostasis well elucidated, but most plants have little information about. Thus, the aim of this study is to describe the use of medicinal plants in patients of an anticoagulation clinic and study the effect of selected plants in blood coagulation in vitro and its phytochemical profile. A calculated sample size of 273 patients were interviewed between May and October of 2014 and 67% of them reported use of medicinal plants. Most of the use of herbs is in the form of tea (87%) and the indication is usually due to the popular knowledge, passed from mother to son (53%). On rare times, this use was indicated by health professionals, revealing the lack of supervision of such use. The most common uses involved treatment of respiratory (34%) and central nervous (32%) disorders. 64 plants were cited and most of them did not have studies in the scientific literature about the influence on blood homeostasis. Of the aforementioned, 18 species plants, choosen by big number of citation and low number of scientific studies, were selected to be extracted by maceration in ethanol. The ethanol extracts were evaluated, in vitro, as the influence in the prothrombin time (PT) and activated partial thromboplastin time (aPTT) tests. Most of these plants demonstrated anticoagulant effect, increasing at least one of the parameters evaluated. Among these plants, which showed a more pronounced effect of increasing the value of aPTT were Citrus sinensis, Lippia alba, Mentha crispa, Mikania laevigata and Nasturtium offinacinale. The essential oil of these species were also evaluated and, in turn, showed less pronounced activities compared to the extracts, highlighting Lippia alba in TP and Citrus sinensis on APTT. In the phytochemical evaluation of these species, the chemical profiles were obtained by high-performance liquid chromatography and thin layer chromatography. Some substances have been identified in coinjection experiments and their relationship to blood homeostasis was discussed. The ethanol extract of L. alba was fractionated and fractions demonstrated anticoagulant activity, mainly dichloromethane fraction. Therefore, it is clear beyond a relevant use of medicinal plants of warfarin users and a large potential of these plants to interfere in anticoagulation treatments. Thus, it is important to monitor the use of these plants and better study their effects on the human body.